Dual Metalation in a Two-Dimensional Covalent Organic Framework for Photocatalytic C–N Cross-Coupling Reactions - Jati, Ayan; Dey, Kaushik; Nurhuda, Maryam; Addicoat, Matthew A; Banerjee, Rahul; Maji, Biplab (Journal of the American Chemical Society, 2022)
Covalent organic frameworks (COFs) are promising hosts in heterogeneous catalysis. Herein, we report a dual metalation strategy in a single two-dimensional-COF TpBpy for performing a variety of C–N cross-coupling reactions. [Ir(ppy)2(CH3CN)2]PF6 [ppy = 2-phenylpyridine], containing two labile CH3CN groups, and NiCl2 are used as iridium and nickel-metal precursors, respectively, for postsynthetic decoration of the TpBpy COF. Moving from the traditional approach, we focus on the COF-backbone host for visible-light-mediated nickel-catalyzed C–N coupling reactions. The controlled metalation and recyclability without deactivation of both catalytic centers are unique with respect to previously reported coupling strategies. We performed various photoluminescence, electrochemical, kinetic, and Hammett correlation studies to understand the salient features of the catalyst and reaction mechanism. Furthermore, theoretical calculations delineated the feasibility of electron transfer from the Ir center to the Ni center inside the confined pore of the TpBpy COF. The dual metal anchoring within the COF backbone prevented nickel-black formation. The developed protocol enables selective and reproducible coupling of a diverse range of amines (aryl, heteroaryl, and alkyl), carbamides, and sulfonamides with electron-rich, neutral, and poor (hetero) aryl iodides up to 94% isolated yield. The reaction can also be performed on a gram scale. Furthermore, to establish the practical implementation of this approach, we have applied the synthetic strategy for the late-stage diversification of the derivatives of ibuprofen, naproxen, gemfibrozil, helional, and amino acids. The methodology could also be applied to synthesize pharmacophore N,5-diphenyloxazol-2-amine and Food and Drug Administration-approved drugs, including flufenamic acid, flibanserin, and tripelennamine.